The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.2175/wer.64.6.11
|View full text |Cite
|
Sign up to set email alerts
|

The case for anaerobic reduction of oxygen requirements in biological phosphorus removal systems

Abstract: zyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA Laboratory and pilot-plant scale studies were conducted to investigate the occurrence of anaerobic reduction of oxygen requirements in excess biological phosphorus removal (BPR) systems. The investigation was accomplished through application of chemical oxygen demand (COD)/oxygen-utilization mass balance techniques. Reductions of 0 to approximately 50% in the oxygen required for organic stabilization were achieved during treatment of synthetic and raw wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Reduction of organic matter in the anaerobic and anoxic zones established conditions for nitrification in the aerobic zone. In the anaerobic zone, a portion of the COD was stabilized, and denitrification consumed COD in the anoxic zone as reported by Randall et al (1992a). The exact magnitude of anaerobic and anoxic COD removal was not calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of organic matter in the anaerobic and anoxic zones established conditions for nitrification in the aerobic zone. In the anaerobic zone, a portion of the COD was stabilized, and denitrification consumed COD in the anoxic zone as reported by Randall et al (1992a). The exact magnitude of anaerobic and anoxic COD removal was not calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Given the quality of our N mass balances ͑again, assuming an f N of 0.1239͒, analytical error of this magnitude seems unlikely. This COD mass balance discrepancy may have been due to the poorly understood and controversial phenomena of "anaerobic stabilization" ͑loss of COD in anaerobic zones; Randall et al 1992; Barker and Dold 1995͒.…”
Section: Effects Upon Oxygen Consumption Sludge Production and Cod mentioning
confidence: 99%
“…The investigation conducted by Randall et al (1992) found that the oxygen requirements of biological phosphorus removal systems may be reduced substantially by processes occurring in the anaerobic reactors. This reduction is in addition to any oxygen credit achieved by denitrification.…”
Section: Organic Removalmentioning
confidence: 99%